2019
DOI: 10.1128/aem.03137-18
|View full text |Cite
|
Sign up to set email alerts
|

Farm Stage, Bird Age, and Body Site Dominantly Affect the Quantity, Taxonomic Composition, and Dynamics of Respiratory and Gut Microbiota of Commercial Layer Chickens

Abstract: The digestive and respiratory tracts of chickens are colonized by bacteria that are believed to play important roles in the overall health and performance of the birds. Most of the current research on the commensal bacteria (microbiota) of chickens has focused on broilers and gut microbiota, and less attention has been given to layers and respiratory microbiota. This research bias has left significant gaps in our knowledge of the layer microbiome. This study was conducted to define the core microbiota colonizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 75 publications
5
102
0
Order By: Relevance
“…Previous studies have shown that early exposures of chickens to stress (i.e., in commercial hatcheries) have prolonged effects later in life and that chickens negatively respond to stress at different maturities ( Ericsson et al., 2016 , Hedlund et al., 2019 ). Likewise, age and body site drive major shifts in the chicken gut and lung microbiota ( Awad et al., 2016 , Ngunjiri et al., 2019 ). However, changes in biological markers of stress and disease susceptibility as well as shifts in the mature hen microbiome between early, peak, and late laying stages have not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that early exposures of chickens to stress (i.e., in commercial hatcheries) have prolonged effects later in life and that chickens negatively respond to stress at different maturities ( Ericsson et al., 2016 , Hedlund et al., 2019 ). Likewise, age and body site drive major shifts in the chicken gut and lung microbiota ( Awad et al., 2016 , Ngunjiri et al., 2019 ). However, changes in biological markers of stress and disease susceptibility as well as shifts in the mature hen microbiome between early, peak, and late laying stages have not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The chicken gut and lungs are 2 of the primary barriers between pathogens and the host ( Bingula et al., 2017 ). Factors such as age may influence the composition of these commensal communities ( Awad et al., 2016 , Kers et al., 2018 , Ngunjiri et al., 2019 ). The overgrowth of pathogenic bacteria in these sites is detrimental to both chicken health and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In early life it is generally observed that the caeca contain high abundances of Enterobacteriales [9,10] and over the first few weeks of life these decline and members of the Clostridiales come to predominate [9][10][11][12][13][14][15][16], with some studies also showing a large increase in Bacteroidetes [12,17,18]. However, the results from some studies do not entirely follow this pattern [19,20] and variability in microbiota composition between flocks can be high [21,22]. Several studies have also examined samples from the small intestine which are less rich and diverse than caecal samples and contain a high abundance of Lactobacilli [12,14,17,18,20,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the study on the digestive system of chickens and turkeys demonstrated that age and environment appear to play a key role in the initial stages of turkey bacterial microbiome maturation [17,29]. In other studies, significant differences in the richness and diversity of respiratory track communities were observed between age groups but in the nasal cavity of chickens [15]. However, the tracheal community composition shifted very gradually as the chicken aged.…”
Section: Sample Collectionmentioning
confidence: 86%
“…The growing number of studies on the avian microbiome demonstrates the influence of the gastrointestinal and respiratory microbiome on the proper development and efficiency of poultry production. In recent years the studies on the bacterial microbiome of poultry have primarily focused on chickens [12][13][14][15]. Particularly focused on the composition and diversity of intestinal microbiome of chickens [11,16].…”
Section: Introductionmentioning
confidence: 99%